Protein enrichment of fruit peels as animal feed supplement by mixed phanerochaete chrysosporium and Schizophyllum commune - Saheed, Olorunnisola Kola; Jamal, Parveen; Abdul Karim, Mohammed Ismail; Alam, Md. Zahangir; Muyibi, Suleyman Aremu (2015)
Optimization of basidiomycete mixed cultures for production of animal feed supplement in a solid state fermentation (SSF) remained elusive. Process conditions associated with improved protein enrichment of fruit peels by two white rot fungi were optimized using response surface methodology (RSM). Through one-factor-at-a-time (OFAT) method, six day fermentation period and temperature of 32°C were optimum for elevated protein synthesis and enzyme activities. Face-Centered Central Composite Design (FCCCD) was used to determine levels and effects of process parameters: pH, inoculum size and moisture content on the protein enrichment of fruit peels. A highly significant quadratic model obtained from FCCCD described optimization path. Results of the statistical analysis showed a significant (P < 0.05) linear effect for pH and inoculum size; while pH and moisture content significantly (P < 0.01) interact. The optimum process combination was found to be 70.2% (v/w) of moisture content, a pH of 5.4 and 6.1% (v/w) inoculum size. A maximum protein content of 198.77 mg/g was obtained during 6-day of solid-state fermentation. Amino acid concentration of the optimized product suited supplement for broiler feed.